Karakteristik Ibu Berdasarkan Ketepatan Pemberian MP-ASI - wijayati, wahyu (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The accuracy of providing complementary feeding contributes to one of the efforts to fulfill parenting patterns, especially for infants, so that optimal growth and development are achieved. This achievement cannot be separated from the characteristics of the mother, such as age, parity, education, occupation, and knowledge of complementary feeding. This study aims to determine the characteristics of mothers based on the accuracy of providing complementary feeding to infants aged 6–12 months at TPMB Fitri Anggraini, Pulau Baru Village, East Oku Regency, South Sumatra Province. This study is a descriptive study. The study population was all mothers who had infants aged 6–12 months at TPMB Fitri Anggraini, Pulau Baru Village, East Oku Regency, South Sumatra Province, totaling 58 mothers. The sample size was 53 mothers, with the Purposive Sampling technique. Independent variables include maternal characteristics (age, parity, education, occupation, whether or not they have received information and knowledge) and the accuracy of providing complementary feeding. The location of the study was carried out at TPMB Fitri Anggraini, Pulau Baru Village, East Oku Regency, South Sumatra Province. The research time was in November 2024. Data collection using a questionnaire, and the data was presented as a percentage. The results of the study showed that from a total of 53 respondents, based on the appropriateness of providing MP_ASI to infants aged 6-12 months, the most data findings were with maternal characteristics (age 26-35 years as many as 21 (39.6%), College Education as many as 19 (35.9%), Self-employed work as many as 25 (47.2%), Primiparous parity as many as 21 (39.6%), Good knowledge as many as 29 (54.7%). A mother has an important role in the appropriateness of providing MP-ASI according to the baby's age, this can have an impact on the health and growth and development of the baby; where the characteristics of the mother include: age, parity, occupation, education, knowledge and other factors can contribute to the appropriateness of providing MP-ASI to infants aged 6-12 months; as one of the efforts to optimize their growth and development.